Latvians and the Soviet System in the 1970s and 1980s: Challenges of Adaptation and Collaboration - Bleiere, Daina (Genocidas ir rezistencija, 2026)
This article examines the current state of research and debate on cooperation with the Soviet regime in Latvia through the application of Stanley Hoffmann’s concepts of collaboration and collaborationism. The main objective of this article is to identify the challenges of analysing collaboration in Latvia during the 1970s and 1980s, taking into account the changing social environment, societal adaptation to the Soviet system and shifts in government policy. Whereas collaborationism is commonly understood as unquestioning submission to the Soviet system, collaboration developed in Latvia as a strategy for preserving national identity under the pressures of Russification.